Determination of Teaching Strategies Considered Necessary in Teaching Biology - Zarovsan Babayeva (Ömer Gökhan Ulum, 2023)
The article talks about the necessity of defining a suitable strategy for teaching biology and other natural sciences with various experiments and research methods, which has a positive effect on the clear understanding of biological concepts in the teaching of biology for the 21st century education. In addition to basic education, traditional methods and tools, methodology, application of methodology at the level of modern standards, new training technologies, and the use of rapidly changing digitalization opportunities have gained relevance in higher and secondary educational institutions. For this, the pedagogical staff's methodical approaches to the evaluation of the students' activities should be changed, and the transformation of biological education into skills should be in the center of attention. It is known that various methods, tools and technologies are used to study living things. Of these, observation, experiment, measurement, microscopy research method, etc. as a basic tool allows for more detailed learning. With these research methods, the researcher obtains wider scientific knowledge about the object or event he is studying. The article also includes interesting examples, tables, schemes that can positively affect the formation of biological knowledge, skills and habits in the teaching of biology.